The 4Ms of an Age-Friendly Health System. Issue 11 (November 2021) - Emery-Tiburcio, Erin E.; Mack, Laurin; Zonsius, Mary C.; Carbonell, Ellen; Newman, Michelle
Abstract : This article is the first in a new series, Supporting Family Caregivers in the 4Ms of an Age-Friendly Health System, published in collaboration with the AARP Public Policy Institute as part of the ongoing Supporting Family Caregivers: No Longer Home Alone series. The 4Ms of an Age-Friendly Health System (What Matters, Medication, Mentation, and Mobility) is an evidence-based framework for assessing and acting on critical issues in the care of older adults across settings and transitions of care. Engaging the health care team, including older adults and their family caregivers, with the 4Ms framework can help to ensure that every older adult gets the best care possible, is not harmed by health care, and is satisfied with the care they receive. The articles in this new series present considerations for implementing the 4Ms framework in the inpatient hospital setting and incorporating family caregivers in doing so. Resources for both nurses and family caregivers, including a series of accompanying videos developed by AARP and the Rush Center for Excellence in Aging and funded by the John A. Hartford Foundation, are also provided. Nurses should read the articles first, so they understand how best to help family caregivers. Then they can refer caregivers to the informational tear sheet— Guide to the 4Ms of an Age-Friendly Health System for Family Caregivers —and instructional videos, encouraging them to ask questions. For additional information, see Resources for Nurses . Abstract : This article—the first in a new series published in collaboration with the AARP Public Policy Institute—outlines the 4Ms of an Age-Friendly Health System framework and how it can be implemented by the health care team, including nurses and family caregivers, in the inpatient hospital setting.